Remdesivir-bisPropionate, a better derivative of remdesivir against SARS-CoV-2: Comparison of in vitro and in vivo PK/PD Study as well as its therapeutic potential - Ashok Chakraborty; Anil Diwan; Vijetha Chiniga; Vinod Arora; Yogesh Thakur; Jayant Tatake; Rajesh Pandey; Preetam Holkar; Neelam Holkar (PLoS ONE, 2026)
FDA approved remdesivir, which was though very effective against SARS-corona virus in cell culture system but in human its efficacy was below 10%, as reported. The main reasons are due to the poor stability of remdesivir in presence plasma. In order to increase the protective strength of remdesivir we took couple of approaches, one, to make an alternative but better derivative of remdesivir as remdesivir bis-propionate, and the other is to use our platform- designed biopolymer (NV387) to protect remdesivir compound from degradation in presence of plasma. Here we present our results as: (1) Remdesivir-bP is much more stable in vivo compared to remdesivir alone. (2) Remdesivir-bP when encapsulated within biopolymer, NV387, its stability is further enhanced. (3) The antiviral activity is also increased against NL-63 infection to rat model, compared to naked and/or encapsulated remdesivir. (4) The antiviral efficacy of the remdesivir pro-drug, therefore, can be mathematically drawn as follows: remdesivir-bP-encapsulated > remdesivir-encapsulated > remdesivir-bP > remdesivir.